2017
DOI: 10.4271/2017-32-0082
|View full text |Cite
|
Sign up to set email alerts
|

Potential of a Production DI Two-Stroke Engine Adapted for Range Extender and Motorcycle Applications

Pierre Duret,
Stéphane Venturi,
Antonio Sciarretta
et al.

Abstract: <div class="section abstract"><div class="htmlview paragraph">The main purpose of this paper will be to investigate if a small snowmobile gasoline Direct Injected (DI) two-stroke engine has the potential to be adapted for two other types of applications: as a range extender (REX) for electric vehicles and for a motorcycle application.</div><div class="htmlview paragraph">For the REX application, the main requested specifications (NVH, lightweight, compactness, minimum production cost an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In terms of oxides of nitrogen emissions two-stroke cycle engines regularly exhibit significant advantage over equivalent comparable four-stroke engines as discussed by Furuhama and Kobayashi, 11 Zhang and Zhao, 12 Duret et al 13 and Mattarelli et al, 14 Benajes et al 15 and Hooper et al 16 Extremely low NOx emissions have been observed from two-stroke engines such as the Lotus Omnivore as reported by Blundell et al 11 and Turner et al 12 This engine operated with variable compression ratio with single digit ppm NOx emissions on 95RON gasoline with further research on bio-fuels indicating similarly low NOx emissions. NOx emissions recorded from experimental stepped piston engines 16 has shown that the engine type shares the advantage of low levels, however the results observed via modelling in this study, whilst showing reduced levels against the fourstroke engine model, do not show such a marked reduction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In terms of oxides of nitrogen emissions two-stroke cycle engines regularly exhibit significant advantage over equivalent comparable four-stroke engines as discussed by Furuhama and Kobayashi, 11 Zhang and Zhao, 12 Duret et al 13 and Mattarelli et al, 14 Benajes et al 15 and Hooper et al 16 Extremely low NOx emissions have been observed from two-stroke engines such as the Lotus Omnivore as reported by Blundell et al 11 and Turner et al 12 This engine operated with variable compression ratio with single digit ppm NOx emissions on 95RON gasoline with further research on bio-fuels indicating similarly low NOx emissions. NOx emissions recorded from experimental stepped piston engines 16 has shown that the engine type shares the advantage of low levels, however the results observed via modelling in this study, whilst showing reduced levels against the fourstroke engine model, do not show such a marked reduction.…”
Section: Discussionmentioning
confidence: 97%
“…In terms of two-stroke engines, little research appears to have been published. Much work has been conducted on bio-fuels as can be seen from the research reported by Misron et al 7 but little on LFG operation apart from the research of Doherty et al 8 A number of researchers have considered natural gas operation of two-stroke engines as evidenced by the work of Douville et al 9 and Darzi et al 10 Engines operating on the two-stroke cycle emit lower emissions of oxides of nitrogen (NOx) than comparable four-stroke cycle engines as demonstrated by the research of Furuhama and Kobayashi, 11 Zhang and Zhao, 12 Duret et al, 13 Mattarelli et al, 14 Benajes et al 15 and Hooper et al 16 Further reduced NOx emissions have been shown by the research of Blundell et al, 17 Turner et al 18 World NOx emissions, from whatever source emits them, can have a particularly adverse effect on global warming (Lammel and Graßl, 19 Collins et al 20 and Bray et al 21 ). Nitrous oxide, N 2 O, reduces ozone occurring in the stratosphere thereby detrimentally affecting the planet's ability to control warming.…”
Section: Introductionmentioning
confidence: 99%